2021
DOI: 10.1007/s11356-021-14996-y
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on Ag/TiO2 photocatalysts: photocatalytic and bactericidal behaviors

Abstract: For many decades, titanium dioxide (TiO 2 ) semiconductor has been extensively applied in several environmental applications due to its higher photocatalytic performances toward different organic pollutants, pharmaceutical compounds, and bacteria. However, its shortfall response to visible light, and the expeditious recombination rate of the photogenerated electron-hole pairs, hampers its utilization. Doping TiO 2 semiconductor with silver nanoparticles is a sound strategy to (1) extend its photocatalytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(144 citation statements)
references
References 148 publications
(190 reference statements)
7
137
0
Order By: Relevance
“…where the letters have their usual meaning, k is a constant, λ is a wavelength of x ray used, β is the FWHM parameter, and θ is the diffraction angle. It has been found that the crystallite size decreases with the increasing concentration of Ag in TiO2 nanocrystals; these results are in good agreement with the previous work [51]. The crystallite size of pure and AgNPs-loaded TiO2 nanocrystals was found in the decreasing order from 18.30 to 13.91 nm with the increase of Ag concentration from 1 to 19%, respectively.…”
Section: Resultssupporting
confidence: 91%
“…where the letters have their usual meaning, k is a constant, λ is a wavelength of x ray used, β is the FWHM parameter, and θ is the diffraction angle. It has been found that the crystallite size decreases with the increasing concentration of Ag in TiO2 nanocrystals; these results are in good agreement with the previous work [51]. The crystallite size of pure and AgNPs-loaded TiO2 nanocrystals was found in the decreasing order from 18.30 to 13.91 nm with the increase of Ag concentration from 1 to 19%, respectively.…”
Section: Resultssupporting
confidence: 91%
“…TiO 2 oxidizes ethylene photo catalytically to produce carbon dioxide and water [49]. This generates reactive oxygen species that are capable of oxidizing ethylene to carbon dioxide and water, whereby TiO 2 must be activated in the presence of oxygen and water with UV radiation along with a wavelength approaching 380 nm [50]. It is unknown precisely how the process related to TiO 2 chemically degrades ethylene.…”
Section: Ethylene Scavenging Mechanismmentioning
confidence: 99%
“…Ag loading on TiO 2 is one of the successful methods to improve the photocatalytic performance of TiO 2 . Ag on the TiO 2 surface can act as an electron trap to trap the electrons transferred from the TiO 2 conduction band; Meanwhile, it creates a surface plasmon resonance (SPR) effect to extend the light absorption to the visible region; In addition, Ag nanoparticles have this excellent antibacterial property [ 32 , 33 ]. Ling et al [ 34 ] reported the preparation of Ag/TiO 2 composites using the photoreduction method for photocatalytic degradation of different organic pollutants and found that Ag could improve the photocatalytic degradation rate, promote the charge separation process, and enhance the adsorption of organic pollutants on the TiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%